Moral Uncertainty - MacAskill, Michael (Oxford University Press, 2020)
Very often, we're uncertain about what we ought, morally, to do. We don't know how to weigh the interests of animals against humans, or how strong our duties are to improve the lives of distant strangers, or how to think about the ethics of bringing new people into existence. But we still need to act. So how should we make decisions in the face of such uncertainty? Though economists and philosophers have extensively studied the issue of decision-making in the face of uncertainty about matters of fact, the question of decision-making given fundamental moral uncertainty has been neglected. In this book, philosophers William MacAskill, Krister Bykvist and Toby Ord try to fill this gap. They argue that there are distinctive norms that govern how one ought to make decisions given moral uncertainty. They then defend an information-sensitive account of how to make such decisions according to which the correct way to act in the face of moral uncertainty depends on whether the moral theories in which one has credence are merely ordinal, cardinal, or both cardinal and intertheoretically comparable. They tackle the problem of how to make intertheoretic comparisons, discussing several novel potential solutions. Finally, they discuss implications of their view for metaethics and practical ethics, and show how their account can shed light on the value of moral enquiry.